(3JeQjf GdWdGH aj UfGYI GdEYQGHs - (3GdLQLGhj GdCRgQj, Rjf GdOjf, NGdO GdCRgQj, NGdO Hf YHO Gddg Hf CHj HcQs
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg GdPQ QaY bOQ ef CYQH GdTgH (B.... (3CeG HYO, aEf eYQaI GdEYQGH ef GdhGLHGJ GdJj dcd WGdH Yde efgGs
(3BNQgG (B:s
(3BNQgG(B: (3hbGd GdTGWHj HYO Cf dYd Cfg QSe eUOQ (B..(3hdYdg eKd HQQI hYdi cd JbOjQ aj GdNjQI fYJ KGfj dUMHI dG ddefJLHjf NdGa ddechOj(B. (3hgPG BNQ eG CQOfGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B2: 297s
(3cTa GdXfhf, L (B1: 483s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdfMhs